Live Everyday to the Full - Lau, MD, Michelle (North American Journal of Medicine and Science, 2009)
Dr. Michelle Lau emigrated from Hong Kong to the United States in 1994. She graduated from UC Berkeley with Highest Honor in Molecular and Cell Biology (Genetics). She graduated from Duke University Medical School in 2004. During her medical school years, she was awarded Clinical Research Training Program Fellowship at the National Institutes of Health. Her research in bone marrow transplant was published in the journal Blood. She is also the regional director of Asian Pacific American Medical Student Association (APAMSA). She then completed her residency in Internal Medicine at Washington University Barnes Jewish Hospital. Her work in sickle cell disease was presented in the American College of Physician Missouri Annual Conference. She is currently finishing her fellowship in Hematology/Oncology at Harvard’s teaching hospital,Beth Israel Deaconess Medical Center. She is honored in this year’s Cambridge Who’s Who list. She is currently performing research on Cancer and Asian Americans.